(untitled) (Editora Impacto Científico, 2025)
This study analyzes the role of Religious Education in promoting spirituality, ethics, and respect for diversity within the Brazilian educational context. It is a bibliographic research based on contemporary authors and normative documents, aiming to investigate how faith and spirituality can contribute to ethical and civic formation when approached in a non-confessional manner. The analysis covered legal, philosophical, and pedagogical aspects, highlighting the importance of confessional neutrality and the appreciation of religious plurality in teaching practices. The results indicate that, although Brazilian legislation ensures secular Religious Education, its implementation still faces challenges related to teacher training and the persistence of confessional approaches. It was found that spirituality, when addressed respectfully and dialogically, can foster moral development, a sense of belonging, and democratic coexistence. It is concluded that overcoming confessionalism, combined with integrative pedagogical practices grounded in listening and dialogue, is essential for Religious Education to be consolidated as a formative space and a promoter of human rights. DOI: https://doi.org/10.56238/edimpacto2025.090-022